The impact of crude oil returns on monetary policy variables in Iraq for duration 2004-2020 - saed Noor, Ali; Jabbar Al- Hussainy, Hashim (Iraqi Journal for Administrative Sciences, 2024)
Iraq is a classic example of the contradiction between the abundance of natural resources and the distortion of the results of economic development and the development of the financial and monetary structure, despite the fact that Iraq is the fifth in the world in crude oil reserves and the second largest crude oil producer in the Organization of Petroleum Exporting Countries (OAPEC), amid all this abundance of natural resources However, the economic policies concerned with the oil sector file have largely failed to live up to expectations and ambitions, and in light of the great importance that the Iraqi oil sector enjoys, the study aimed to know the impact of the shocks of crude oil revenues on monetary policy variables. And that is by measuring the correlation and effect between crude oil revenues and monetary policy variables, which include money supply, inflation, exchange rates in the parallel market, interest rates on deposits for a period of six months and interest rates on savings deposits for banks operating in Iraq, depending on the data of the study, which includes (17) year of oil revenues, by using a set of standard analyzes by means of statistical programs. The study reached a set of results, the most important of which is the presence of A strong direct correlation and effect between Iraqi oil revenues and money supply, which is consistent with the logic of economic theory in rentier countries, where the statistical results indicate that the hypotheses had a statistical significance at the level of morality used (5%).